Multivariance solutions for designing new levels of coal mines (Rudarsko-geološko-naftni zbornik, 2020)
In this article, variants of technological designing of new mining enterprise levels for obtaining the skills of engineering task execution are considered. The complex approach for the justification of a mine’s parameters is examined. The com- binations of quantitative and qualitative parameters for designing new coal-face and preparation works, transport, ven- tilation, and draining-out of gases, pumping, and mineral deposits while keeping cost reduction in mind for all stages of mining enterprise operations are presented. The obtained results allow us to lay the foundations for optimizing the pa- rameters of the development system and the rational order for the coal reserves, under the changing mining and geo- logical conditions of coal field deposit development. Conclusions regarding the implementation of the multivariance solutions in new coal mine level designing are made on the basis of undertaken investigations. The obtained results with sufficient accuracy in a practical application can be used to determine the development of new coal mine levels.